The history of the cape Supreme Court and its role in the development of judicial precedent for the period 1827-1910 - Fine, Hilton Basil (Department of Public Law, 2018)
In commenting on the effect of the Royal Charter of Justice of 1827, Hahlo and Kahn state that 'within a lustrum the legal institutions of the Cape had been transmogrified’. However a number of important changes had already been made to these institutions in the period preceding the 'lustrum'. It is apparent that the legal institutions at the Cape were already being altered during the First British Occupation which lasted from September 1795 to February 1803.